Living the live with healthy experiences: New-age elderly in Germany - Loureiro, S.; Middendorf, J. (Proceedings of the International conference on Tourism and Ageing., 2016)
The aims of this study are to analyze which potential attributes of anti-ageing experiences (goods, services, experiences) will tend to be associated to subjective happiness; how cognitive age is associated to mindfulness; and the influence of mindfulness on subjective happiness.